Evaluasi Program Sanitasi Total Berbasis Masyarakat Stop BABS Di Puskesmas Lanjut Kecamatan Singkep Pesisir Kabupaten Lingga Tahun 2020 - Devis, Yesica; Alhidayati, Alhidayati; Maulana, M. Farhan (STIKes Surya Global Yogyakarta, 2021)
Background of Study: STBM is an approach to change hygienic and sanitary behavior through community empowerment by means of triggering. Based on data from the Riau Islands Provincial Health Office in 2019, Lingga Regency is among the highest with 93% of villages implementing STBM, or there were 76 villages out of a total of 82 villages that have implemented STBM. The aims of this research is to determine the level of knowledge and behavior of respondents in an objective or verbal. Methods : This research method was descriptive qualitative research by means of interviews and observations. Results : The results of this study were sufficient human resources in carrying out the STBM Stop BABS program. An adequate budget for program implementation. Infrastructure that does not meet the needs of health workers. Policies that are not in accordance with the requirements that have been set. Conclusion : The STBM program has been carried out by socialization to encourage the community to avoid open defecation which aims to achieve an Open Defecation Free (ODF) condition and monitoring is carried out by the puskesmas every 3 months. The target was not achieved due to the absence of village regulations stipulating the STBM Stop BABS program and the lack of experience of health workers. The village should make regulations related to the STBM program and special training for health workers. Keywords : Program Evaluation, STBM, Advanced Puskesmas, Singkep, BABS